Gouverner un territoire de l’eau à partir de considérations sur les savoirs liés à la production du paysage - Jacques-Aristide Perrin (Projets de Paysage)
This article focuses on the effects on waterscapes of the application of a public environmental policy referred to as the ecological continuity of waterscapes. Implemented since the beginning of 2010, this policy is intended to create favourable conditions for the circulation of migratory fish and sediments. Generating conflicts in the case of certain operations, it involves multiple issues encompassing political and scientific dimensions. Following a study carried out between 2014 and 2017 monitoring operations of ecological continuity in the Dordogne and Têt catchment areas, we analysed the consequences of this type of operation on landscapes and on water uses, which sometimes involve significant modifications in the case of the destruction of hydraulic works. Given how landscape issues are addressed in the implementation of this policy, its current framework does not make it possible to depart from a sector-based management approach focused on biodiversity. To this end, using field observations, we put forward a proposal focused on landscape-related knowledge as a method for implementing this public policy governing waterscapes.